The influence of collaborative constructivist approaches on improving science learning outcomes in slow learners in elementary school - Prasetyo, Sigit; Nurdin, Indra Fajar; Noviar, Dian; Abroto (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas PGRI Mahadewa Indonesia, 2025)
This research is motivated by the low value of science learning outcomes for students who are slow to learn, compared to those of their peers. This study aims to investigate how the collaborative constructivist approach can enhance science learning outcomes and effectively apply it to meet the learning needs of students who are slow learners. The method used is an experimental quasi-design in the form of a Nonequivalent control group design. The population in this study consisted of 42 children, divided into 18 children from 2 treatment elementary schools and 24 children from 2 control elementary schools. Data was obtained from the results of the Pretest and post-test. The use of non-parametric statistical analysis techniques involves two statistical test techniques: the Mann-Whitney test and the Wilcoxon signed rank test. The study results indicate that the collaborative constructivist approach can enhance natural science learning outcomes for children with learning difficulties in inclusive elementary schools. Proven through the analysis test of the Mann-Whitney statistical test and the Wilcoxon Signed Rank Test, the result is significant at 0.000 < 0.05. means there is a practical difference in improving natural science learning outcomes. Thus, teachers need to be equipped with related training on mastering the collaborative constructivist approach in teaching slow learners in inclusive elementary schools to strengthen their mastery of concepts and the development of the potential possessed by slow learners, as needed, and to enable them to enjoy the presence of other children socio-psychologically.